Platão escritor, a escritura de Eros - Telló, Arthur Beltrão (2023)
This work proposes a reading of The Symposium, by Plato, considering this dialog as a literary work and it´s author not as a philosopher who writes, but as a philosophical writer or as a writing philosopher, according to the stylist richness present in some of the platonic texts, especially in The Symposium, Phedro and Phedon. Reflecting on concepts such as mimesis, discourse and language, this work opposes the banishment of the poets proposed by Plato in The Republic with the understanding that Plato himself was a gifted poet, capable of assuming different forms and, therefore, ironically, someone to be banished by his own self. In this sense, from the figure of Eros as the search for what we lack, Plato articulates a literary text filling the spaces of knowledge through writing.